Research on the relationship between sensory profile and physicochemical properties of paocai, a Chinese fermented vegetable. Issue 12 (13th October 2019) - Chen, An‐jun; Luo, Wei; Niu, Kai‐li; Peng, Yi‐tao; Liu, Xing‐yan; Shen, Guang‐hui; Zhang, Zhi‐qing; Wan, Hu; Luo, Qing‐ying; Li, Shan‐shan
Abstract: Paocai is a popular fermented vegetable side dish or appetizer in China. This study was to investigate the relationship between its sensory quality and physicochemical properties by different statistical methods and to establish a regression prediction model for sensory scores. Principal component analysis disclosed that the sensory properties were negatively correlated with lactic acid and acetic acid contents. The cluster analysis classified the samples into three groups based on their sensory scores and the main differences among the groups were firmness, salinity, and acid production. Finally, a prediction model with an adjusted R 2 of 85.28% was established by partial least squares regression to predict the sensory scores and showed high reliability on six tested samples. Practical applications: Paocai is a popular side dish or appetizer in China that has a large annual production and consumption. Nowadays, the evaluation of the quality of paocai is mainly relied on sensory assessment, which is expensive to implement, time‐consuming, and sometimes cannot be implemented online for immediate feedback. By establishing the relationship between sensory quality and physicochemical properties of paocai, it is possible to build online feedback of paocai production by instrumental detections.